Pseudonimizacja jako nowy środek zabezpieczenia danych osobowych w świetle zmian prawnych w UE – wybrane aspekty - Niedźwiecki, Mateusz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article is about question of pseudonymization which is a way of protecting personal data. It means the processing of personal data in such a manner that the personal data can no longer be attributed to a specific data subject without the use of additional information, provided that such additional information is kept separately and is subject to technical and organisational measures to ensure that the personal data are not attributed to an identified or identifiable natural person. This concept appears for the first time in the new EU regulation of 2016. The article presents main changes related to new regulation, describes the process of pseudonymization as well as selected methods of its use. It also presentes disadvantages that may be associated with this technique. The author also refers to the practical aspect citing the results of a study commissioned by Dell in 2016 on the new regulation
Keywords: pseudonymization; personal data protection; regulation; amendment; GDPR